Comparative proteomics of soluble factors secreted by human breast adipose tissue from tumor and normal breast - Fletcher, Sabrina Johanna (2018)
Tumor progression depends on the tumor-stroma interaction. In the breast, adipose tissue is the predominant stromal type. We have previously demonstrated that conditioned media (CMs) from explants of human adipose tissue of tumor breasts (hATT) increase proliferation and migration of breast cancer epithelial cells when compared to human adipose tissue from normal breasts (hATN). In this work, we aim to identify specific proteins and molecular/biological pathways associated with the secretion profile of hATT and hATN explants. hATT-CMs and hATN-CMs were separated by SDS-PAGE and analyzed by means of two-dimensional nano-liquid chromatography-mass spectrometry. The data was analyzed using ProteoIQ and FunRich software. In addition, 42 cytokines from hATTCMs and hATN-CMs were assayed by a protein antibody assay. Compared to hATNCMs, hATT-CMs showed greater protein diversity. We found that hATT-CMs presented a greater amount of proteins related to complement system activity, metabolism and immune system, as well as proteins involved in a variety of biological processes such as signal transduction and cell communication. Specifically, apolipoprotein AI and AII, complement component 3, and vimentin and desmin were significantly increased in hATT-CMs versus hATN-CMs. Moreover, a multivariate discriminant analysis of the cytokines detected by the array showed that IL-6, MCP-2 and GRO cytokines were sufficient and necessary to differentiate hATT-CMs from hATN-CMs. This analysis also showed that the levels of these three cytokines, taken together, correlated with stage and histological grade of the tumor in the hATT-CMs group, and with body mass index in the hATN-CMs group.